Multistage vector (MSV) therapeutics - Wolfram, Joy (J Control Release, 2015)
One of the greatest challenges in the field of medicine is obtaining controlled distribution of systemically administered therapeutic agents within the body. Indeed, biological barriers such as physical compartmentalization, pressure gradients, and excretion pathways adversely affect localized delivery of drugs to pathological tissue. The diverse nature of these barriers requires the use of multifunctional drug delivery vehicles that can overcome a wide range of sequential obstacles. In this review, we explore the role of multifunctionality in nanomedicine by primarily focusing on multistage vectors (MSVs). The MSV is an example of a promising therapeutic platform that incorporates several components, including a microparticle, nanoparticles, and small molecules. In particular, these components are activated in a sequential manner in order to successively address transport barriers.